การตรวจโปรตีน พี53 ในน้ำเลือด เพื่อใช้เป็นปัจจัยทำนายการตอบสนองที่ไม่ดีต่อการรักษาผู้ป่วยไทยที่เป็นโรคมะเร็งตับด้วยวิธี ทีโอซีอี - ธีรยุทธ นัมคณิสรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Objective to study serum p53 protein as a predictive for unfavorable response to transarterial oily chemoembolization (TOCE) in patients with hepatocellular carcinoma. Methods The populations consisted of new cases of hepatocellular carcinoma who were treated with transarterial oily chemoembolization at Radiology Intervention Unit. Department of Radiology. King Chulalongkorn Memorial Hospital during the 1" January 1999 and the 31" December 1999. With the expectation that the test would have sensitivity of at least 90 % and on least than 15 % error, the sample size was 38. Serum was kept prior the chemoembolization. Serum p53 protein was blindly measured by ELISA method in picogram per milliliter. Data was analysed by statistical methodology to calculate sensitivity, specificity, positive and negative predictive values. Results: There were 45 hepatocellular carcinoma patients enrolled into this study. Thirty-two were male and thirteen were female. Male per female ratio was 2.45: 1. The median of age was 59 years and mean of age was 56.42 years. (Range 31-74 years). Risk factors consisted of hepatitis B virus in 24 cases (53.3%), hepatitis C 6 cases (13.3%) and history of alcoholic consumption 12 cases (26.7%). Twenty-eight cases (62.2%) were associated with cirrhosis. TNM stagings were stage 11 4.4%, stage IIIA 42.2 %, and stage IVA 53.3%. Okuda stagings were stage 1 40%, stage 11 55.6%, and stage 111 4.4%. Median serum alpha-fetoprotein level was 351.95 IU/ml. (range1.6-400000 IU/ml). Forty-one of pre-chemoembolization p53 serum were kept and serum p53 protein was detected in 10 cases (24.4%). The ranges of p53 protein were 5-1147 pg/ml. Forty-one cases were evaluable for tumor response to TOCE and achieved a partial response of 41.46%. Thirty-seven patients had information both serum p53 and the response of the treatment. Patients who had a positive p53 test had a response rate only 33.3% whereas the patients with negative p53 test had a response rate of 50%. How ever, the p-value was 0.462 by Fisher s exact test. The serum p53 protein test has sensitivity of 30.0%, specificity of 82.3%. positive predictive value of 66.7 % and negative predictive value 50%. Conclusions 1. The serum p53 protein by ELISA test to determine the response of chemoembolization has 30.0 % of sensitivity. 82.3% of specificity. 66.7 % of positive predictive value and 50 % negative predictive value. 2. Serum p53 protein, which is measured by ELISA, cannot be used as a predictive factor for unfavorable response to transarterial oily chemoembolization. However, there is a trend of lower response rate to chemoembolization if the serum p53 test is positive.